PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING (STUDI PADA PERUSAHAAN AKR CORPORINDO TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020) - Howardi Visza Adha; Juliman Jaya Zai (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2023)
The scope of this research is a study of the effet of profitability (ROE) and liquidity (CR) on firm value (PBV) with capital structure (DER) as an intervening variable at AKR Corporindo Tbk in 2016-2020. The purpose of this study was to determine the effect of profitability (ROE) and liquidity (CR) on firm value (PBV) with capital structure (DER) as an intervening variable that analyzes the pattern of relationships between variable in the form of cause and effect and with the aim of knowing the direct effect and indirect. This research is a quantitative research with a path analysis approach. Based on the results obtained from substructure one, it shows that partially profitability (ROE) has no significant effect on capital structure (DER). Liquidity (CR) partially has a negative and significant effect on capital structure (DER) and the combined effect of profitability (ROE) and liquidity (CR) on capital structure (DER) is 79,8%. Partial profitability (ROE) has a positive and significant effect on firm value (PBV), liquidity (CR) partially has a negative and significant effect on firm value (PBV) and capital structure (DER) partially has a negative and significant effect on firm value (PBV). The combined effect of profitability (ROE), liquidity (CR) and capital structure (DER) variables on firm value (PBV) is 30,2%.